Pengaruh Sosialisasi Peraturan Daerah dan Kualitas Pelayanan Pengaduan terhadap Kepatuhan Masyarakat dalam Menjaga Ketertiban Umum di Kecamatan Sagulung, Kota Batam - Chandra, Roli; Maileni, Dwi Afni; Bhakti, Rizki Tri Anugrah; Hutasoit, Isfandir (Lembaga Teewan Journal Solutions, 2026)
This study examines the effect of local regulation socialization and complaint service quality on community compliance in maintaining public order in Sagulung District, Batam City. The study is grounded in the argument that community compliance is not determined solely by sanctions, but also by citizens' understanding of regulations, the quality of government communication, service responsiveness, and trust in local law enforcement. A quantitative survey design was employed. Data were collected using Likert-scale questionnaires administered to 120 residents of Sagulung District and analyzed with IBM SPSS Statistics through validity and reliability tests, descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The findings show that local regulation socialization has a positive and significant effect on community compliance. Complaint service quality also has a positive and significant effect and emerges as the more dominant predictor. Simultaneously, both variables explain 64.2% of the variance in community compliance. These findings confirm that effective public order enforcement requires a combination of regulatory education and complaint services that are responsive, transparent, accessible, and accountable. This study contributes to empirical legal studies and local public administration by positioning complaint services as an instrument for shaping social compliance rather than merely an administrative reporting channel.